Electrical Detection of Magnetic Skyrmions in a Magnetic Tunnel Junction (Adv. Electron. Mater. 1/2023). (10th January 2023) - Guang, Yao; Zhang, Like; Zhang, Junwei; Wang, Yadong; Zhao, Yuelei; Tomasello, Riccardo; Zhang, Senfu; He, Bin; Li, Jiahui; Liu, Yizhou; Feng, Jiafeng; Wei, Hongxiang; et al.
Abstract : Skyrmion Hosts An approach to tailor skyrmion‐host materials and magnetic tunnel junctions (MTJs) is proposed by Giovanni Finocchio, Guoqiang Yu, and co‐workers in article number 2200570 . The skyrmion in the host material can be successfully imprinted into the free layer of the MTJ and read out via the tunneling magnetoresistance. This work demonstrates a highly efficient scheme to detect magnetic skyrmions with an MTJ via spin texture imprinting.